The advanced of audio visual learning media for children development examination by using pre screening developmental questionnaire for midwifery students - Yuliasti Eka Purnamaningrum; Munica Rita Hernayanti (Jurnal Kesehatan Ibu dan Anak, 2018)
The number of children under five years in Indonesia is approximately 10 percent from the overall population; therefore it needs serious attention to improve the quality of their development as these children will become the next generation of the nation. The examination of child development by using Pre-screening developmental questionnaire (Kuesioner Pre Screening Perkembangan (KPSP) is one of the competences of the midwivesTo improve the quality of student learning outcomes, teachers should provides creative and interesting learning sources which are easily understood by the students. Video is one of the learning media considered more effective to use because it stimulates sight, hearing, and kinesthetic (movement) at one time (at a time). Further, it enables open discussion among students and facilitators. This research aimed to produce a product of audio visual learning media or video material used in child examination by using KPSP. The type of research undertaken is product-oriented research and development.Research is conducted by involving the product design stage, product making and development, and product evaluation. The research findingsare (1) the audio visual media or learning video used for teaching child development by using KPSP, (2) material experts, media experts, education experts and students state that video as the learning media to explain child development by using KPSP is considered feasible. Audio-visual media of children's developmental examination materials using KPSP can be used as an alternative learning media to improve students' motivation and creativity in improving child's developmental examination skills.